Energetics in elite race walkers. Issue 8 (3rd August 2022) - Etxebarria, Naroa; Spratford, Wayne; Iriberri, Jon; Ross, Meg; Gomez-Ezeiza, Josu; Pyne, David
ABSTRACT: Race walkers must conform to a unique gait pattern with no visible loss of contact with the ground. However, how the gait pattern affects the race walking economy is unclear. We investigated the energy cost (amount of energy spent per distance unit) at different race walking velocities and over a 25 km hybrid walk. Twenty-one international-level male race walkers ( V ˙ O2peak 63.8 ± 4.3 ml kg −1 min −1, age 31 ± 5 y, body mass 68.1 ± 7.0 kg) performed an incremental treadmill test consisting of 4 × 4 min submaximal stages with 1 km h −1 increments, and a 25 km submaximal hybrid walk (treadmill-overground) on separate days. Energy cost was measured continuously during the submaximal test and at km 0–1, 6–7, 12–13, 18–19, 23–24 of the 25 km hybrid walk. The C RW was similar across the four submaximal stages where half the athletes completed them at a higher (1 km h −1 ) absolute velocity (−0.01–0.15 ± ∼0.65); range of standardised differences ±90% CL, with a tendency for higher performing athletes to have a lower C RW when this was analysed during absolute race walking velocities of 12, 13 and 14 km −1 for the entire cohort (0.46–0.49 ± ∼0.67). There was no substantial change in C RW from the start to the end of the 25 km walk for the entire cohort (0.08 ± 2.2; standardised change ±90% CL). Elite race walkers are characterised by having a similar energy cost among athletes who perform at the same relative exercise intensity, and substantially higher energetics than counterpart elite endurance runners.